Every child, every classroom, every day : school leaders who are making equity a reality - 4 0 16; 1945- , Peterkin, Robert,;Jewell-Sherman, Deborah,;Kelley, Laura,;Boozer, Leslie; 5 (San Francisco : Jossey-Bass, 2011)
It takes readers through the profession of superintendent from entry to exit and includes information on communicating the vision, strategic planning, instructional reform, engaging the community, allocating resources, collaborating with unions and school boards, replicating success, and sustaining improvement.--Provided by publisher.
Includes bibliographical references and index.
Professional;Professional.
System requirements for PC and Mac stated on p. 293.
Keywords: 2 -- 0; 6; School superintendents and principals;School management and organization;Educational leadership -- United States.; United States.;United States; 20; 2